A novel method for cardiac vector velocity measurement: Evaluation in myocardial infarction. (July 2016) - Cruces, Pablo Daniel; Arini, Pedro David
Abstract : Highlights: The concept of quaternion is used for computing the angular velocity of the tip of the cardiac vector. Independent parameters are extracted from the XYZ orthogonal leads and are combined for the design of a general index of cardiac vector velocity. Alterations in the dynamics of the cardiac vector provoked by a myocardial infarction can be detected optimally with high sensitivity and specificity. Abstract: Background and objective: Pathological alterations provoked by myocardial infarction cause slow conduction by increasing axial resistance on coupling between cells. This issue may cause abnormal patterns in the dynamics of the tip of the cardiac vector. Methods: In this work, we have developed a method to compute the angular velocity during ventricular repolarization from Frank XYZ leads, using the concept of quaternion. This parameter jointly with the linear velocity obtained by differentiation and the spatial velocity reported by others during ventricular depolarization, have been combined in order to design a myocardial infarction detector (so-called index of cardiac vector velocity: ICVV) with high values of sensitivity and specificity simultaneously. Results: The predictive power of ICVV has been tested in two groups: patients with less than 7 days after infarction, achieving 98% of sensitivity and 97% of specificity; and patients with more than 45 days after infarction, achieving 92% of sensitivity without loss of specificity. The former group is important for early detection of myocardial infarction and begins treatment in a short period of time on emergency department. The latter involves the evaluation of the cardiac vector velocity after the period of post-infarction electrical remodeling which may be useful in the follow-up of patients. Conclusions: We have concluded that this method extends the concept of cardiac vector velocity and may be useful in the diagnosis of myocardial infarction.